SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Elisa Elisa; Heni Pujiastuti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study systematically examines students' mathematical problem-solving abilities through the application of the Discovery Learning model. The method used was a Systematic Literature Review of indexed scientific articles from 2021-2026 that were relevant to the research topic discussing problem-solving, mathematics learning, and exploration in students. The search was conducted through national and international databases using a combination of keywords such as Discovery Learning and Mathematical Problem Solving, then selected through the stages of identification, screening, and determining eligibility according to predetermined inclusion criteria. The synthesis of the results of this study indicates that students' mathematical problem-solving abilities are generally still in the moderate category and are not optimal, accompanied by weaknesses in the stages of understanding problems, planning strategies, and opening. The application of the Discovery Learning model has been proven to contribute positively to improving problem-solving abilities through active student involvement in independent exploration and discovery of concepts. In addition, the Discovery Learning model has an effect on improving problem-solving and resolution of mathematical problems. However, the effectiveness of the Discovery Learning model is influenced by several factors such as teacher readiness, student initial abilities, and supportive learning conditions. This study emphasizes the importance of designing student-centered learning and encouraging exploratory activities to develop students' mathematical problem solving optimally. ABSTRAK Penelitian ini mengkaji secara sistematis kemampuan pemecahan masalah matematis siswa melalui penerapan model pembelajaran Discovery Learning. Metode yang digunakan adalah Systematic Literature Review terhadap artikel-artikel ilmiah terindeks pada rentang tahun 2021-2026 yang relevan dengan topik penelitian yang membahas pemecahan masalah, pembelajaran matematika, dan eksplorasi pada siswa. Pencarian dilakukan melaui basis data nasional dan internasional yang menggunkan kombinasi kata kunci seperti Discovery Learning dan Mathematical Problem Solving, kemudian diseleksi melalui tahapan identifikasi, penyaringan, dan penentuan kelayakan sesuai dengan kriteria inklusi yang telah ditetapkan. Sintesis hasil kajian ini menunjukkan bahwa kemampuan pemecahan masalah matematis siswa secara umum masih berada pada kategori sedang dan belum optimal yang disertai dengan kelemahan pada tahap memahami masalah, merencanakan strategi dan mengevaluasi. Penerapan model pembelajaran Discovery Learning terbukti memberikan kontribusi positif dalam meningkatkan kemampuan pemecahan masalah melalui keterlibatan aktif siswa dalam eksplorasi dan penemuan konsep secara mandiri. Selain itu model pembelajaran Discovery Learning berpengaruh terhadap peningkatan dalam memecahkan serta menyelesaikan suatu permasalahan matematika. Namun efektivitas penerapan model pembelajaran Discovery Learning dipengaruhi oleh beberapa faktor seperti kesiapan guru, kemampuan awal siswa, dan kondisi pembelajaran yang mendukung. Kajian ini menegaskan pentingnya perancangan pembelajaran yang berpusat pada siswa dan mendorong aktivitas eksploratif mengembangkan pemecahan masalah matematis siswa secara optimal.